2012
DOI: 10.1186/1756-3305-5-296
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and associated risk factors among pregnant women in Gilgel Gibe dam area, Southwest Ethiopia

Abstract: BackgroundAnaemia is known to be one of the outcomes of parasitic infection and it may result in impaired cognitive development, reduced physical work capacity and in severe cases increased risk of mortality, particularly during the prenatal period. The aim of this study was to determine the prevalence and associated risk factors of anaemia among pregnant women in Gilgel-Gibe dam area, southwestern Ethiopia.MethodsA cross-sectional community based study was conducted on 388 pregnant women living in three distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
84
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(144 citation statements)
references
References 10 publications
36
84
16
Order By: Relevance
“…This is in line with findings from a study conducted in Ethiopiamalariaparasitaemia increases the risk of anaemia in pregnant women by 11.2 times [23].Similarly, other studies have reported that being positive for malaria parasitaemia increases the risk of anaemia [25,27].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with findings from a study conducted in Ethiopiamalariaparasitaemia increases the risk of anaemia in pregnant women by 11.2 times [23].Similarly, other studies have reported that being positive for malaria parasitaemia increases the risk of anaemia [25,27].…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of anaemia found in this study was higherthan the 53.9% prevalence reported in Ethiopia [23].The currentstudy revealed pregnant women who were 30-39 years were 42% times less likely to have anaemia (AOR=0.58, p=0.040),whichisin contrast with the high risk of anaemia with respect to the same age group in Turkey [24]. This study also revealed that pregnant women in their second trimester were 1.39 times more likely to have anaemia (AOR-1.39, p=0.043),which is consistent with a study conducted where pregnant women in their second trimester were 2.87 times more likely to be anaemic [25].…”
Section: Discussioncontrasting
confidence: 54%
“…There was a significant correlation between increasing hookworm parasite load, A. lumbricoides and T. trichiura and decreasing hematocrit values. This shows that as the helminth parasitic load increased the hematocrit level decreased; as a result the risk of developing anemia increase 28 . In general, those regions with high prevalence of anemia are lowlands and coastal regions where the soil is sandy.…”
Section: Hookworm Infectionmentioning
confidence: 93%
“…This finding is high but comparable with other local studies carried out in different parts of Ethiopia. In a study undertaken in the Gilgel Gibe dam area, (53.9%) of pregnant woman were anemic in Asendabo (62.7%), and in Jimma (57%) anemia prevalence was reported in pregnant women attending ANC clinics (17)(18)(19). Similar findings were also reported in eastern Sudan (62.6%) and China (70%); India also reported a higher result than this study (92.39%) (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%